Ergonomics Status of Indonesian Forestry Workers: Physical-Mental-Social Fatigue, Job Satisfaction, Concept of Hazards, and Concept of Accident Cost - Efi Yuliati Yovi (Jurnal Ilmu Kehutanan)
Sustainable forest management requires attention to the protection of occupational safety and health (OSH), in addition to attention to aspects of work productivity, and the welfare of managers/workers. In Indonesia, these four aspects, which are the main objectives of ergonomics studies, have not received much attention, although forest management activities are activities with a high risk of OSH disorders. This study aims to present an overview of the conditions of physical-mental-social fatigue, musculoskeletal disorders (MSDs), job satisfaction, perception of hazards sources, and perception toward work accident costs from workers involved in forest management activities in Indonesia. Fatigue status was measured using the Cumulative Fatigue Symptom Index (CFSI) and MSDs were investigated using Standardized Nordic Questionnaire (SNQ). Job satisfaction, perception of the source of danger, and the cost of accidents were traced using questionnaires and interviews (face to face, open and semi-structured questions). Data were taken from 98 respondents consisting of forest rangers, forest inventory workers, logging supervisors, and administrative staff during February 2016–October 2017. The CFSI analysis shows that forest guarding and forest inventory have caused intense physical and mental fatigue (in the form of excessive anxiety). The SNQ analysis confirms intense MSDs complaints at the waist, back, neck, shoulders, and arm. The general characteristics of the respondents were having: (1) limited financial capacity, (2) inadequate knowledge to recognize various potential hazards sources at work, and (3) inappropriate understanding of the concept of accident costs. The limitations on the respondents’ cognitive, has made participatory OSH mechanisms alone (to improve OSH protection) is not an appropriate option. Efforts to improve OHS protection should be carried out in the form of (1) improving workplace facilities (health facilities, social and communication facilities, accessibility), (2) improving remuneration, and (3) improving knowledge on the concepts of the source of hazards and accident cost.